Properties of the Extremely Energetic GRB 221009A from Konus-WIND and SRG/ART-XC Observations - D. Frederiks; D. Svinkin; A. L. Lysenko; S. Molkov; A. Tsvetkova; M. Ulanov; A. Ridnaia; A. A. Lutovinov; I. Lapshov; A. Tkachenko; V. Levin (The Astrophysical Journal Letters, 2023)
We report on Konus-WIND (KW) and Mikhail Pavlinsky Astronomical Roentgen Telescope – X-ray Concentrator (ART-XC) observations and analysis of a nearby GRB 221009A, the brightest γ -ray burst (GRB) detected by KW for >28 yr of observations. The prompt, pulsed phase of the burst emission lasts for ∼600 s and is followed by a steady power-law decay lasting for more than 25 ks. From the analysis of the KW and ART-XC light curves and the KW spectral data, we derive time-averaged spectral peak energy of the burst E _p ≈ 2.6 MeV, E _p at the brightest emission peak ≈ 3.0 MeV, the total 20 keV–10 MeV energy fluence of ≈0.22 erg cm ^−2 , and the peak energy flux in the same band of ≈0.031 erg cm ^−2 s ^−1 . The enormous observed fluence and peak flux imply, at redshift z = 0.151, huge values of isotropic energy release E _iso ≈ 1.2 × 10 ^55 erg (or ≳6.5 solar rest mass) and isotropic peak luminosity L _iso ≈ 3.4 × 10 ^54 erg s ^−1 (64 ms scale), making GRB 221009A the most energetic and one of the most luminous bursts observed since the beginning of the GRB cosmological era in 1997. The isotropic energetics of the burst fit nicely both “Amati” and “Yonetoku” hardness–intensity correlations for >300 KW long GRBs, implying that GRB 221009A is most likely a very hard, super-energetic version of a “normal” long GRB.